Caravans : A Novel - Michener, James A. (London Corgi Books, 1976)
"Combining fact with riveting adventure and intrigue, Michener follows a military man tasked, in the years after World War II, with a dangerous assignment: finding and returning a young American woman living in Afghanistan to her distraught family after she suddenly and mysteriously disappears."--Back cover.
Keywords: a